Analisis Semiotika Pesan Akhlak Dalam Film Kartun Riko the Series Pada Youtube Episeode “Adab Sebelum Ilmu” - Handayani, Safitri; Jailani, Muhammad (eScience Humanity Journal, 2024)
Children are a category of people who are very adaptive to stimuli from the surrounding environment, such as movies and games. However, today many publish video content that displays inappropriate and unpleasant content that can endanger character values in children. This study aims to analyze the form and character message conveyed in the film Riko The Series episode “Adab Before Science” in improving character value education in children. This research uses a descriptive qualitative approach with Charles Sanders Peirce's semiotic technique. The results showed that the film Riko The Series episode “Adab Before Science” conveyed various forms of good character such as gratitude which shows positive behavior as an important part of good character, helping, giving advice, and forgiving each other, as well as bad character such as impoliteness which emphasizes the negative impact of impoliteness and instills the importance of mutual respect, the second is the attitude of irritability which must be avoided because anger teaches will harm ourselves and can damage relationships with others. The third is prejudice, which is an attitude that can undermine the trust of others. Through strong semiotic signs consistent with normative ethical theory, it not only teaches important moral values but also shows their relevance in children's daily lives.